Striking a Balance : Managing El Niño and La Niña in Philippines’ Agriculture - Sutton, William R. (World Bank, Washington, DC, 2019)
The purpose of this report is to improve the Philippines’ preparedness for the El Niño–Southern Oscillation (ENSO) by informing stakeholders of ENSO’s agricultural and economic impacts. The report finds that ENSO has detrimental impacts on the Philippine people, economy, poverty levels, and agricultural sector. The country has taken actions and enacted policies to respond to ENSO events, but these have not adequately mitigated the costs of ENSO impacts. That said, there are further actions the country can take to better prepare for these impacts. This is important because of the Philippines’ high exposure to climate shocks, the rural population’s climate vulnerability, and the prominence of the agricultural sector in the national economy.